Pulmonary multiple cystic lesions in a patient with Behçet's syndrome - M.E. Tezcan; B. Isci (PAGEPress Publications, 2019)
Pulmonary involvement, mainly originating from vasculitis, is one of the features of Behçet's syndrome (BS). We describe, for the first time in literature, computerised tomography images of a male BS patient with multiple pulmonary cystic lesions possibly originated from vasculitis or bronchiolar stenosis.